The Impact of Bureaucratic Restructuring on Public Services and Organizational Performance at the Regional Office of the Ministry of Religion in NTT Province - LENGARI, Yoseph Wilh P.; DJANI, William; SAYRANI, Laurensius P. (PT Keberlanjutan Strategis Indonesia, 2023)
Bureaucratic restructuring must be able to produce a structure that is lean, flexible, responsive and efficient. However, this has not yet happened to the Regional Office of the Ministry of Religion of the Province of NTT, so an in-depth study is needed regarding the impact of bureaucratic restructuring on organizational performance at the Regional Office of the Ministry of Religion of the Province of NTT based on changes in the dimensions of the organizational structure. The method used in this research is a qualitative research method, the type of data in this research is qualitative data and quantitative data and the data sources in this research are primary data and secondary data. The results of the study found that changes in the dimensions of the organizational structure by Robbins (1994:89-91) on: (a) the complexity aspect was found in terms of vertical differentiation, namely that there were still tasks for echelon III structural officials directly delegated to functional officials because they were not there are structural echelon IV officials so that all services are still running as before the restructuring occurred, (b) in the aspect of formalization it was found that the functional positions resulting from the restructuring were only